Humic substances of differently matured composts produced from municipal solid wastes and biomass of energetic plants - Kałuża-Haładyn Andrea; Jamroz Elżbieta; Bekier Jakub (Soil Science Annual, 2019)
The aim of the study was to assess the transformation of humic substances during composting of biomass of energetic plants and municipal solid waste. The type of the organic material to be composted and the type of technology used affect the course of the humic substances transformation and formation of compost maturity parameters. Compost produced from the mixture of energetic willow and hay biomass contained humic substances with higher share of low-molecular fractions and lower share of humic acids in total organic carbon than those produced from municipal solid wastes. Obtained results also showed that insoluble alkali fraction plays an important role in humification process by its convertion to a new humic substances. Share of humic and fulvic fractions in relation to the total organic carbon appears to be reliable indicator of composting as a process of enhancing organic matter humification.